Selenium in tea plant cultivation: bioavailability, uptake, metabolism, and physiological regulation - An, Lijin; Mao, Yingxin; Huang, Danjuan; Leng, Yang; Chen, Xun (Frontiers in Plant Science, 2025)
Selenium (Se) is a trace element essential for human health. Incorporating Se into the tea (Camellia sinensis (L.) O. Kuntze) cultivation has emerged as a cropping technology in the area of agriculture and food sciences. The production of Se-enriched tea is greatly influenced by Se bioavailability in tea garden soil, which in turn influences the Se assimilation, absorption, and transportation of tea plants. Recent studies reported that Se can regulate tea plant growth by altering soil microbes, thereby improving soil fertility and enhancing tolerance to abiotic stressors such as pesticide toxicity, fluoride toxicity, and temperature extremes. Selenium can modulate the secondary metabolism of tea and design Se-rich functional components, which determine the quality of Se-enriched tea. This review seeks to provide theoretical bases for optimizing Se management in tea gardens and the cultivation of Se-enriched tea.